2008
DOI: 10.1002/uog.5275
|View full text |Cite
|
Sign up to set email alerts
|

Increasing accuracy of antenatal ultrasound diagnosis of cleft lip with or without cleft palate, in cases referred to the North Thames London Region

Abstract: Objectives To determine the accuracy of antenatal ultrasound diagnosis of cleft lip with or without cleft palate (CL ± P) and isolated cleft palate (CP). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
5
11
0
Order By: Relevance
“…Overall, 39.2% (87/222) of cases of unilateral or bilateral CL ± P were not detected in the antenatal period. This is similar to recently published data by Demircioglu et al 11. Chmait et al 10 reported a 21.6% rate of undiagnosed associated structural abnormalities.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, 39.2% (87/222) of cases of unilateral or bilateral CL ± P were not detected in the antenatal period. This is similar to recently published data by Demircioglu et al 11. Chmait et al 10 reported a 21.6% rate of undiagnosed associated structural abnormalities.…”
Section: Discussionsupporting
confidence: 92%
“…Success could be achieved via teaching the parents and providing support to face such challenges 10,11,12,13 . In this study the prenatal diagnosis was confirmed in 37% of the affected cases, that rate was coincide with several previous studies which showed a range from 19% to 70% with correspondence to the design of the study 14,15,16,17 .…”
Section: Discussionsupporting
confidence: 92%
“…An isolated orofacial cleft is considered to be an anomaly of variable severity, but with a generally good prognosis. Prenatal diagnosis is important to exclude associated anomalies, to define the need for karyotyping or other genetic investigations (for example, to search for 22q11 deletion) and to counsel parents about the prognosis and management25. Prenatal detection enables parents to be adequately prepared for the special feeding requirements of their baby.…”
Section: Discussionmentioning
confidence: 99%